Consecutive Interpretation: A Discourse Approach. Towards a Revision of Gile’s Effort Model - Wu, Guangjun; Wang, Kefei (Meta, 2009)
AbstractIn reality, expert interpreters from time to time do successfully tide over the gap between the capacity required and capacity available in dealing with extraordinarily large segments in consecutive interpretation. These exceptional cases imply that Gile’s Effort Model does not always hold and requires to be supplemented. This paper attempts to: 1) advance a solution to the dilemma that, in processing large segments in consecutive interpreting, the working memory capacity available is more often than not smaller than the capacity required, hence supplementing Gile’s Effort Model; 2) specify the rules of discourse transformation in consecutive interpretation; based upon the features of memory and consecutive interpretation, we deem that each segment, be it large or small, shall be processed as a discourse, the transformation of which is presumed to be the said solution; 3) and subsequently identify the optimal discourse transformation model, which is both capable of embodying the source text to the largest extent possible and achievable in terms of memory load. In addition, the author, through an observational study, justified the hypothesis. The validity of this theory, however, still requires further experimental evidence.